USEFULNESS OF INTELEUKIN 6 TO AVOID INNECESARY ANTIBIOTIC TREATMENT IN NEONATAL SEPSIS OF VERTICAL TRANSMISSION - marta costa-romero (Mediterranean Journal of Hematology and Infectious Diseases)
Objective In the presence of risk factors of neonatal sepsis of vertical transmission, antibiotic treatment is usually started. The main purpose of this study was to evaluate the usefulness of Interleukin 6 (IL6) to avoid unnecessary antibiotic treatment. Study design We conducted a prospective study among patients admitted to the Neonatal Intensive Care Unit. In total, 73 patients were included. Infants were classified as belonging to one of three subgroups: infected, not-infected and control group. Values of IL6, C reactive protein and Procalcitonin were collected. We calculated the optimal cut-off point using the receiver operating curve. Likelihood ratio and odds ratio has been calculated, as well as classical parameters of diagnostic efficiency. Results Significantly higher serum IL6 levels were detected in the infected group. Septic neonates were 5-fold more likely to have a positive IL6 than healthy newborns and their post-test probability was 9-fold higher than pre-test probability. A negative IL6 concentration virtually ruled out sepsis despite the presence of risk factor for vertical sepsis. Conclusion IL6 could be used to ruling out sepsis in asymptomatic neonates with risk factor for vertical sepsis, avoiding excessive antibiotic treatment.